Piezoelectric Fixing Direction effect on GRF test results in Wearable Shoe-Insole System - Kubba, Ammar Issam Salih (Al-Nahrain Journal for Engineering Sciences, 2022)
This article is about studying the placing direction effect of a piezoelectric sensor on the shoe insole in the GRF results. Where the sensors used in this research are in two directions, along and perpendicular to the foot midline. In the both cases the sensors were fixed on the shoe insole to sense the foot pressure. For the first set of sensors which are perpendicular to the foot midline the collected data has similar trend to the GRF collected from the force plate, as the small lateral strain in the shoe insole due to the patient weight and GRF is close to the GRF data collected from other measurement system. On the other hand, the collected data from the second set of sensors which are in a longitudinal direction with the foot midline will have different trend and values from the collected data from the force plate or any other GRF measurement system. This different in the results is due to the large longitudinal strain in the shoe insole due to the patient weight which produce dissimilar results from the force plate result data.